Avaliação da união entre o componente protético e a conexão interna tipo cone morse do implante dentário - Gois Filho, Derivaldo Moura (2015)
The biomechanical aspects related to the adaptation of fixed prostheses over implants are directly associated to treatment success. Therefore, the aim of this study was to evaluate the presence of microgaps in the union formed by the abutment and the inner connection of Cone Morse dental implant. The study was composed by two groups. The first group (n:16) used materials (dental implant and abutment) of the same manufacturer, Neodent® (Curitiba-PR, Brazil). The second group (n:16) used materials from different manufacturers, where the dental implant was Neodent® (Curitiba-PR, Brazil), and the abutment was Singular®(Parnamirim-RN, Brazil). The sets were sent to scanning electron microscope (SEM), where it was taken the measurements of microgaps formed between the implant connection and the abutment. The results obtained were submitted to statistical (Mann-Whitney-U) evaluating dispersion measurements and central tendency of values (standard and mean deviation). In group 1 the average found was 5,69μm and standard deviation (SD) was 8,46μm. Group 2 showed average of 1,24μm and SD: 0,44μm. The group formed by dental implant and abutment from the same manufacturer showed a greater data dispersion, with greater microgap values, compared to the group formed by the set implant-abutment of different manufacturers. It was concluded that, based on the measurements taken on SEM, the group formed by implant and abutment of different manufactures showed lower values of microgaps, and, therefore, a better in vitro adaptation.